CASE REPORTSConcomitant surgical treatment of a chondrosarcoma of the chest wall and a desmoid tumor of the gastrointestinal tract - Sadowski, Andrzej; Chruścicka, Iwona; Rak, Piotr; Ptach, Anna; Maliszewski, Daniel; Pęksa, Rafał; Haponiuk, Ireneusz; Zieliński, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
The co-existence of a chondrosarcoma of the chest wall and a desmoid tumor in the gastrointestinal tract is rare. In both Polish and global literature, cases of chest wall chondrosarcomas are presented in the form of case reports. Desmoids of the gastrointestinal tract are more common; notwithstanding, their incidence in Europe is estimated at approximately 2 cases per 1 million inhabitants per year. We present the case of a 62-year-old female patient who suffered from both a chest wall chondrosarcoma and a desmoid tumor of the intestine; both neoplasms were operated on simultaneously. The former tumor was located in the region of the right costal margin, whereas the latter was located in the mesojejunum. The surgery was performed with two independent surgical incisions. The postoperative period was uneventful. The case is noteworthy in view of the extremely rare synchronous occurrence of the described tumors and due to the fact that any such operation requires an individualized surgical approach.